Competing Germanies : Nazi, antifascist, and Jewish theater in German Argentina, 1933-1965 - Kelz, Robert Vincent (Ithaca : Cornell University Press : Cornell University Library, 2019)
"Following World War II, German antifascists and nationalists in Buenos Aires believed theater was crucial to their highly politicized efforts at community-building, and each population devoted considerable resources to competing against its rival onstage. Competing Germanies tracks the paths of several stage actors from European theaters to Buenos Aires and explores how two of Argentina's most influential immigrant groups, German nationalists and antifascists (Jewish and non-Jewish), clashed on the city's stages. Covered widely in German- and Spanish-language media, theatrical performances articulated strident Nazi, antifascist, and Zionist platforms. Meanwhile, as their thespian representatives grappled onstage for political leverage among emigrants and Argentines, behind the curtain, conflicts simmered within partisan institutions and among theatergoers. Publicly they projected unity, but offstage nationalist, antifascist, and Zionist populations were rife with infighting on issues of political allegiance, cultural identity and, especially, integration with their Argentine hosts"--
Introduction : Argentina's competing German theaters -- German Buenos Aires asunder -- Theater on the move : routes to Buenos Aires -- Staging dissidence : the Free German Stage -- Hyphenated Hitlerism : transatlantic Nazism confronts cultural hybridity -- Enduring competition : German theater in Argentina, 1946-1965.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 27, 2020).
JSTOR
Keywords: Freie Deutsche Buehne in Buenos Aires -- History; Deutsches Theater (Buenos Aires, Argentina) -- History; Freie Deutsche Buehne in Buenos Aires; Ethnic theater -- Argentina -- History -- 20th century; National socialism and theater -- Argentina -- History; Jewish theater -- Argentina -- History -- 20th century; Germans -- Argentina -- History -- 20th century; German drama -- 20th century -- History and criticism; Théâtre ethnique -- Argentine -- Histoire -- 20e siècle.; Nazisme et théâtre -- Argentine -- Histoire; Théâtre juif -- Argentine -- Histoire -- 20e siècle.; Allemands -- Argentine -- Histoire -- 20e siècle.; Théâtre allemand -- 20e siècle -- Histoire et critique; LITERARY CRITICISM -- European -- German; Ethnic theater; German drama; Germans; Jewish theater; National socialism and theater; Argentina; 1900-1999; Migration studies, Buenos Aires, Gelmanistic, theater history, Free German Stage, Zionist culture; Criticism, interpretation, etc; History